2015
DOI: 10.1039/c4ew00027g
|View full text |Cite
|
Sign up to set email alerts
|

A fixed bed column study for the removal of Pb2+ ions by watermelon rind

Abstract: The present study reports the feasibility of removing Pb 2+ ions from aqueous solution using watermelon rind (WR) as a low cost adsorbent. Fixed bed column studies were employed to study the removal efficiency of Pb 2+ ions by varying the column parameters such as flow rate, bed height and initial metal ion concentration. The results showed that breakthrough and exhaustion time increases with a decrease in flow rate, inlet concentration, and an increasing bed height. The breakthrough curves obtained were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
1
36
1
1
Order By: Relevance
“…It was studied that breakthrough time decreases (20–10 min) with increasing flow rate. Similarly, saturation time decreases from 75–45 min .…”
Section: Fixed‐bed Column Processmentioning
confidence: 98%
See 1 more Smart Citation
“…It was studied that breakthrough time decreases (20–10 min) with increasing flow rate. Similarly, saturation time decreases from 75–45 min .…”
Section: Fixed‐bed Column Processmentioning
confidence: 98%
“…It was shown that metal ion sequestration increases from 11.7 to 15.2 mg g −1 for CIF‐R and from 20.4 to 30.4 mg g −1 for CIF‐BC with increased metal concentration. Lakhshmipathy and Sarada observed that increases in the inlet concentration (500–700 mg L −1 ) increase the uptake capacity of metal ions (45.3–55.0 mg L −1 ).…”
Section: Fixed‐bed Column Processmentioning
confidence: 99%
“…The model is based on hypothesis that the Cr(VI) is directly adsorbed onto the Aspergilluscellulose biosorbent where the intra particle diffusion and external mass transfer are negligible and assumes that equilibrium is not attained rapidly [58]. This model is applied more in the depiction of the initial part of the breakthrough curve.…”
Section: Application To Bed Depth Service Time (Bdst) Modelmentioning
confidence: 99%
“…Each experiment was repeated thrice and average values have been reported. The amount of metal adsorbed to prepared adsorbents was determined from Equation (1) and % removal was evaluated by Equation (2).…”
Section: Batch Mode Adsorption Studiesmentioning
confidence: 99%